Evolution of the geomorphology of erodible bedform submitted to fluid - Liu, Z.-C.; Fan, W.-J. (Archives of Mechanics, 2014)
A coupled map lattice (CML) model was developed to study the evolution of desert’s geomorphology. The numerical results show that the model presents abundant spatiotemporal patterns. In spatial behaviors, the model illustrates the mechanism of both weakly and strongly coupled systems. In temporal behaviors, the model illustrates the stochastic effects. The model is able to demonstrate the physically layered coupling mechanism and shows the initiative and driven coupled systems. The evolutional processes of the model are also analyzed with physical geomorphological laws. The desert’s geomorphologic forms, such as sand ripples and dunes, result from the combined actions of deterministic and stochastic effects. Verified by the field data, this study qualitatively illustrates the geomorphologic evolution of desert. Moreover, the model is applicable to the evolution of ripples and dunes with loose sand caused by water currents on fluvial beds, e.g., river beds in the lower reaches of the Yellow River, China.